Towards EU-wide Mandatory Human Rights and Environmental Due Diligence for Business: a Breakthrough in Europe and Beyond? (Polish Yearbook of International Law, 2023)
In March 2022, the European Commission presented its long-awaited legislative proposal on the EU-wide human rights and environmental due diligence (HREDD) for business. This article argues that the proposed Directive fails to be an effective and innovative legislation in three respects. Firstly, it does not draw lessons from the shortcomings of the to-date regulatory policy relating to business and human rights. It mainly consolidates at the EU level the status quo of extant due diligence legislation in Europe. Secondly, the proposal falls short of the established international standards and its own objectives insofar as it fails to establish instruments for effectively preventing and remedying human rights and environmental harm. Thirdly, the proposal’s normative preference for process- (rather than result-) oriented HREDD risks reducing it to yet another compliance instrument. Beside amending these shortcomings, to achieve a breakthrough, the upcoming legislation should in any case define HREDD as the legal standard of care; the compliance with which does not per se exclude civil liability. The general negotiation approach of the Council is not proposing much improvement in that regard. The stakes for the European Parliament’s possible role to raise the bar are thus very high.